1998
DOI: 10.1159/000026173
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Prevalence of Dementia in Two Sicilian Communities with Different Psychosocial Backgrounds

Abstract: The role of education and psychosocial environment as factors for the development of dementia is controversial. We carried out a comparative study on the prevalence of dementia among persons over 74 years of age in two Sicilian municipalities, Troina and S. Agata Militello, with different psychosocial backgrounds. A two-stage survey was performed for both samples. In stage 1 the Mini Mental Status Examination (previously validated for the cutoff score with 100% sensitivity and the highest specificity) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 17 publications
3
33
1
1
Order By: Relevance
“…Higher prevalence values were reported in central Italy [2,3], in 2 Southern Italian communities [5], and in Granarolo [4], a geographical area very close to that of our study. This could be due to the higher proportion of illiterate persons included in these studies.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Higher prevalence values were reported in central Italy [2,3], in 2 Southern Italian communities [5], and in Granarolo [4], a geographical area very close to that of our study. This could be due to the higher proportion of illiterate persons included in these studies.…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with findings from the Italian Longitudinal Study on Aging [6] and a Swedish incidence study [31], this trend was more pronounced for women than for men. In other Italian studies, by contrast, dementia prevalence has been reported to be similar in both sexes [4,5] or higher in men than in women [3].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…MVD also determines volume of possible binding site before docking and cavity with largest volume is selected as docking point. Population of Indian subcontinent has very low risk of AD as compared to other continent of the world (Boersma et al 1998;Brayne et al 1998;Azzimondi et al 1998;Shaji et al 1996;Yamada et al 1999;Woo et al 1998;Lin et al 1998;Fillenbaum et al 1998;Herrera et al 1998;Lopes et al 2007). This may be due to regular consumption of curry spice turmeric and other herbal congeners by Indian population.…”
Section: Structural Conservation Of B-amentioning
confidence: 99%
“…A number of the studies that have been published since 1997 report experience with the MMSE in diff e r e n t populations. [15][16][17] Teresi et al 18 studied item bias in standard cognitive screening measures in a sample of Afro-American, Hispanic and nonHispanic White elderly respondents who were part of a dementia case registry study. The psychometric methods of item-response theory were applied to identify biased items.…”
Section: B What Approaches To Diagnosis Can Be Used Across Cultures?mentioning
confidence: 99%